Pendidikan Budi Pekerti Bagi Anak Dalam Perspektif Novel Laskar Pelangi Karya Andrea Hiarata - Dwi Puji Pangesti; Asep Sunarko; Ngatoillah Linnaja (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to determine the content of the novel Laskar Pelangi, ethics education in the Laskar Pelangi novel, and the application of ethics education in the Laskar Pelangi novel. This thesis uses a qualitative research approach, where the type of research is liberary research. Data collection techniques use documentation methods and online searches. Then, data sources were obtained from primary data derived from the novel Laskar Pelangi by Andrea Hirata and secondary (Children's Moral Education books, theses, articles, internet sites, and journals). Laskar Pelangi is a novel written by Andrea Hirata published in 2005. It tells the story of education and contains motivational messages and enthusiasm to overcome life's difficulties, through perseverance and unyielding spirit. Several elements in the novel illustrate the importance of forming moral values in children, good ethics are considered an important foundation for building individuals who are tough, have integrity, and care for the surrounding environment. The application of ethics education in Laskar Pelangi does not only occur through formal learning in schools, but also through life experiences and social interactions.